2006
DOI: 10.1002/app.24424
|View full text |Cite
|
Sign up to set email alerts
|

Properties of calcium carbonate filled and unfilled polystyrene foams prepared using supercritical carbon dioxide

Abstract: Foaming behaviors of four polystyrenes (PSs) filled and unfilled with various amounts of CaCO 3 using supercritical carbon dioxide were investigated. The PSs include three general purpose grades with different molecular weights (different melt index) and one high impact grade. By adjusting foaming conditions, foam density was determined for each investigated sample. In general, the sample with a lower molecular weight (i.e. higher melt index) yielded a lower foam density for the three general purpose PSs. With… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…With respect to the microcellular foaming, CaCO 3 is a commonly used nucleation agent that can induce cell nucleation and improve cell density during the foaming process. This effect has been reported in PS SC‐CO 2 foaming . However, there have been no reports on the foaming behavior of the PS/SBS/CaCO 3 ternary system.…”
Section: Introductionmentioning
confidence: 59%
“…With respect to the microcellular foaming, CaCO 3 is a commonly used nucleation agent that can induce cell nucleation and improve cell density during the foaming process. This effect has been reported in PS SC‐CO 2 foaming . However, there have been no reports on the foaming behavior of the PS/SBS/CaCO 3 ternary system.…”
Section: Introductionmentioning
confidence: 59%
“…Recent advances in processing of polymer nanocomposite foams enabled new application areas in hydrogen storage [5], electromagnetic shielding [6], and sensing technology [7]. Various polymers are being used in foam applications such as polyurethane, polystyrene, polyethylene, polypropylene, poly(vinyl chloride), polycarbonate, and poly(methyl methacrylate) [8][9][10][11][12][13][14] as well as specialty polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of inorganic nanoparticles, which act as nucleating agents, induces heterogeneous nucleation and provides a large number of nucleation sites. Furthermore, the presence of micro-or nanosized fillers dramatically decreases the energy barrier for cell nucleation compared to that required for homogeneous nucleation [9,13,16,17]. Existing models based on classical nucleation theories sometimes fail to explain the nucleation satisfactorily.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer foams reinforced by fillers such as fibers, clay, talc, CaCO 3 , etc. have been studied and reported [5–9]. Among these fillers, CaCO 3 is of most commonly used mainly for its availability in readily usable form and low cost [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that CaCO 3 could improve the mechanical property of the matrix, and therefore provokes increased mechanical property of polymer foams [7, 10, 11]. Furthermore, CaCO 3 can also increase the melt viscosity of matrix and acts as bubble nucleating agent, which is conducive to foaming [6, 12]. Therefore, polymer foams filled with CaCO 3 have been extensively studied [6, 7, 12–14].…”
Section: Introductionmentioning
confidence: 99%